STUDI KEGIATAN TADARUS AL-QUR’AN DIKALANGAN REMAJA MASJID TAQWA DI KAPALO KOTO KANAGARIAN BALAI GURAH KECAMATAN IV ANGKEK KABUPATEN AGAM - Atika Prihatini; Silfia Hanani (Pascasarjana Universitas PTIQ Jakarta, 2023)
The background of this research problem originates from the Al-Qur'an tadarus activity carried out by teenagers in Kapalo Koto Kanagarian Balai Gurah, IV Angkek District, Agam Regency, including teenagers who are in a mosque youth organization, namely Taqwa Mosque Youth (REMESTA). Al-Qur'an tadarus activities are carried out not only in the month of Ramadan, but are also carried out on ordinary days after prayer and at night related to Al-Qur'an tahsin. The research in this thesis aims to find out how Al-Qur'an recitation is carried out in Al-Qur'an tadarus activities among young people at the Taqwa Mosque in Kapalo Koto Kanagarian Balai Gurah District IV Angkek, Agam Regency. The method used in this study is a qualitative method using data collection techniques, interviews, observation and documentation. The results of the study show that the tahsin of the Qur'an which is carried out in Al-Qur'an tadarus activities among adolescents uses the talaqqi method which can make teenagers better understand the makharijul of letters, the characteristics of letters, and the law of tajwid in the Qur'an, as well as being able to fluent, refine, improve in reading the Qur'an.